PERANAN KOMUNITAS CIKAPUNDUNG DALAM MENGEMBANGKAN KARAKTER PEDULI LINGKUNGAN SEBAGAI WUJUD PEMBANGUNAN BERKELANJUTAN - Bhakti Muslim Wihendar, - (2021)
Environmental problems are increasingly widespread, along with human development in the age of globalization. Environmental crises in major cities are affected by a growing human population due to the high rate of urbanization. If examined again, the development of development in indonesia, especially the city of bandung, the quality of environmental sanitation is getting worse, the quality of the city's surface water and air decreases, this condition is exacerbated by the rate of groundwater production that decreases in the bandung basin area. In indonesia, citizenship education teaches young people to meet the needs of today, without sacrificing the right to meet the needs of future generations. Sustainable development efforts are urgently needed to save generations to come. In order to realize these efforts, it takes planting environmental caring characters. Departing from these problems, this research was conducted to find out the cikapundung community program in developing environmental caring character as a form of sustainable development. This research uses a qualitative approach with case study methods. Data collection techniques conducted in this study by interview, observation, documentation and literature studies. Data analysis techniques are carried out by reducing data, presenting data, drawing conclusions and verification and conducting data validity. The results showed that the cikapundung community has a very large role in instilling the values of environmental care character as a form of sustainable development, evidenced by programs that are routinely carried out by the community with a share of members in it. Keywords: Character Care For The Environment, Sustainable Development, Cikapundung Community.